2021
DOI: 10.1021/acs.iecr.1c02020
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Ratiometric Fluorescent Probe Based on the Two-Isophorone Fluorophore for Sensing Nitroxyl

Abstract: Nitroxyl (HNO) is closely linked with numerous biological processes. Fluorescent probes provide a visual tool for determining HNO. Due to fluorescence quenching by HNO-responsive recognition groups, most of the current fluorescent probes exhibit an “off-on” fluorescence response. As such, the single fluorescence signal of these probes is easily affected by external factors such as the microenvironment, sensor concentration, and photobleaching. Herein, we have developed a ratiometric fluorescent probe (CHT-P) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Conventional HNO detection methods use analytic instruments to quantify products of HNO dimerization/dehydration or reactions with thiols, phosphine, and heme proteins. However, most of them are indirect, time-consuming, and relatively unreliable. To overcome the limitations, direct HNO detection methods based on mass spectrometry and electrochemistry were developed. For detections inside living cells, in vivo HNO sensors are accessible with bioimaging functions using metal complexes, phosphines, thiols, , or esters …”
Section: Introductionmentioning
confidence: 99%
“…Conventional HNO detection methods use analytic instruments to quantify products of HNO dimerization/dehydration or reactions with thiols, phosphine, and heme proteins. However, most of them are indirect, time-consuming, and relatively unreliable. To overcome the limitations, direct HNO detection methods based on mass spectrometry and electrochemistry were developed. For detections inside living cells, in vivo HNO sensors are accessible with bioimaging functions using metal complexes, phosphines, thiols, , or esters …”
Section: Introductionmentioning
confidence: 99%
“…26 Therefore, it is crucial to develop novel uorescent probes for the detection of Al 3+ to overcome these drawbacks. In recent years, isophorone dyes have been used to construct uorescent probes [27][28][29] and electroluminescent (EL) materials 30 due to their ultrafast intramolecular charge transfer (ICT) 31 and large Stokes shis 32 generated by the electron donor-p-acceptor molecular structure. 27,29 However, few studies have been reported on the structure of isophoronebased Al 3+ uorescent probes.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other reported uorescent probes, 20,23,33 the malononitrile-isophorone uorescent probe was used in this study because of its relatively simple synthesis process and similar uorescence properties, which is favourable for wide application. [27][28][29] The dicyanoisophorone derivatives themselves have excellent near-infrared uorescence emission properties. 34 Upon addition of Al 3+ , the probe YT-Al complexes with it, leading to a decrease in the electron absorption capacity of the carbonyl group (C]O), which enhances the ICT effect 31 of the probe molecule and red-shis the uorescence spectrum.…”
Section: Introductionmentioning
confidence: 99%